ASSESSMENT OF HYDROGEN PEROXIDE ON HISTOPATHOLOGY AND SURVIVAL RATE IN COMMON CARP, CYPRINUS CARPIO L. INFECTED WITH SAPROLEGNIASIS - & et al., Mustafa (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
The present study was carried out in order to understand and describe the histological alterations and survival rate in common carp, Cyprinus carpio L. treated with various concentrations of hydrogen peroxide following Saprolegniasis infection. One hundred fish infected with Saprolegnia spp. were collected from fish farms in Babylon/Iraq. Fungal isolation was done from different parts of the body using the routine technique. Pathogenicity of the isolated fungi was tested on host fish with a concentration of 2×104 zoospores L-1 and the fishes were got the infection. Hydrogen peroxide at different concentrations (1, 3, 6 ml/L for 30 min for 3 successive d and control group) was used to control the experimental fungal infection in fish. In addition, formalin (0.15 ml/l for 60 min for 3 successive d interval) was used as a reference treatment. Results showed various histomorphological changes in the gills of the infected and treated fish with H2O2 including degeneration of lamellae, epithelial proliferation, fusion of the secondary lamellae, aneurysm  and cellular necrosis. Similar alterations were seen in fish infected groups and treated with H2O2 or formalin but are significantly decrease (P